Testing for Deliberate Underpricing in the IPO Premarket: A Stochastic Frontier Approach - Hunt-McCool, Janet; Koh, Samuel C.; Francis, Bill B. (Review of Financial Studies, 1996)
We reevaluate the IPO underpricing phenomenon using the stochastic frontier methodology. The advantage of the stochastic frontier is that it can be used to measure the level of deliberate underpricing in the premarket without using after-market information. This is accomplished through the estimation of a systematic one-sided error term that measures “inefficiency” or the difference between the maximum predicted offer price and the actual offer price. Data for the analysis are comprised of 1,035 IPOs of common stock issued by firm commitment between 1975 and 1984. IPOs appear to be deliberately underpriced in the premarket in both hot-market and nonhot-market periods. Moreover, the determinants of the maximum IPO price have different effects in the two time periods.